Graffiti e pixação: diálogos na cidade de São Paulo - Fasano, Bianca Fernandes (2021)
Taking as a cutout the city of São Paulo, its landscape and urban supports, as well as the possibilities of living, occupying and appropriating it, this research has as its object two interventions that are daily present in the metropolises and which manifest an aspect of the experience of urban space, being they graffiti and "pixação". It questions which dialogues these graphic expressions provoke when intervening in the city and is guided by objectives, which analyze these interventions as other ways of understanding and investigating urban spaces. Its perspective is the city as a collective construction, stage of cultural events and a space of possibility for actors and social manifestations (BORJA; CASTELLS, 1996). Through the narratives of graffiti artists and taggers, articulated to the positioning and actions of the government and the movements to institutionalize these practices (CAIAFA; SODRÉ, 2008), we investigate what motivates the various distinctions between these graphic expressions in the dialogues they establish with the space and processes that exalt one over the other. The methodology was guided by field observations carried out online and offline and indepth interviews. It seeks to understand its dynamics, productions and cultural practices (LASSALA, 2010) and the present relationship between the city, its supports and communication with the urban and social environment (PEREIRA, 2010). The importance of the theme is justified because it is based on relevant concepts to the understanding of how and what are the possible ways of occupying and appropriating the city, as well as the various possibilities for the use of its territories (SANTOS, 2006). It considers the transformations and the growing process of expansion of urban art, as well as the construction of paths by these young people to deal with the conception of the graffiti artist as an professional, present in institutional practices, and the preservation of freedom and transgression in intervening and occupying the spaces of the city, seeking agreement between the production without limitations by the city and institutional making. This process enables new ways to observe and read everyday experiences and the dynamics in which they are inserted, reformulating the imagination and forms of occupation of spaces and places in the city (CERTEAU, 1994)